PENGARUH PERSEPSI ATAS PP NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK - Rosella, Vina; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the influence of perception of tax fairness, perception of ease of taxation, andperception of simplicity of taxation which is related to the government regulation No. 46 of 2013 to the level oftax compliance. The hypotheses of this research i.e.: (1) the perception of tax fairness which is related to thegovernment regulation No. 46 of 2013 has positive influence to the level of tax compliance. (2) Perception ofsimplicity of taxation which is related to the government regulation No. 46 of 2013 has positive influence to thelevel of tax compliance. (3) The perception of simplicity of taxation which is related to the government regulationNo. 46 of 2013 has positive influence to the level of tax compliance. The quantitative research is the researchapproach which is used in this research with the multiple linear regression analysis. The primary data have beenobtained by issuing questionnaires to 66 respondents who have been selected by using purposive sampling arethe individual and corporate taxpayers (OP) which are subject to 1% final income tax in accordance with thegovernment regulation No. 46 of 2013 in the area of Surabaya and Sidoarjo. The result of this research showsthat the perception of tax fairness and the perception of simplicity of taxation which is related to the governmentregulation No. 46 of 2013 has positive influence to the level of taxpayer compliance. Meanwhile, the perceptionof simplicity of taxation which is related to the government regulation No. 46 of 2013 does not have anyinfluence to the level of taxpayer compliance.Keywords: the perception of taxation fairness, the perception of ease of taxation, and the perception ofsimplicity of taxation, taxpayer compliance, PP No. 46 of 2013.